2018
DOI: 10.1186/s13063-018-2556-0
|View full text |Cite
|
Sign up to set email alerts
|

Circulating stem cells, HIF-1, and SDF-1 in septic abdominal surgical patients: randomized controlled study protocol

Abstract: BackgroundSepsis caused by complicated intra-abdominal infection is associated with high mortality. Loss of endothelial barrier integrity, inflammation, and impaired cellular oxygen have been shown to be primary contributors to sepsis. To date, little is known regarding the pathway for the mobilization of endothelial progenitor cells (EPCs) from the bone marrow in sepsis whereas stromal-cell-derived factor 1a (SDF-1a) and hypoxia inducible factor 1 (HIF-1) seem to have a role in the EPC response to hypoxic mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Progenitor cell recruitment to injured tissues can be prevented if SDF-1 in ischemic tissue or CXCR4 on circulating cells were blockaded [54,57]. In the bone marrow, discrete regions of the anoxic chamber have increased SDF-1 expression and progenitor cell tropism [58]. Over the last 10 years, numerous studies have confirmed that SDF-1/CXCR4 has a pivotal role in the biologic and physiologic functions of MSC [59].…”
Section: Discussionmentioning
confidence: 99%
“…Progenitor cell recruitment to injured tissues can be prevented if SDF-1 in ischemic tissue or CXCR4 on circulating cells were blockaded [54,57]. In the bone marrow, discrete regions of the anoxic chamber have increased SDF-1 expression and progenitor cell tropism [58]. Over the last 10 years, numerous studies have confirmed that SDF-1/CXCR4 has a pivotal role in the biologic and physiologic functions of MSC [59].…”
Section: Discussionmentioning
confidence: 99%
“…Progenitor cell recruitment to injured tissues can be prevented if SDF-1 in ischemic tissue or CXCR4 on circulating cells were blockaded [55,58] . In the bone marrow, discrete regions of the anoxic chamber have increased SDF-1 expression and progenitor cell tropism [59] . Over the last ten years, numerous studies have con rmed that SDF-1/CXCR4 has a pivotal role in the biologic and physiologic functions of MSC [60] .…”
Section: Discussionmentioning
confidence: 99%
“…Progenitor cell recruitment to injured tissues can be prevented if SDF-1 in ischemic tissue or CXCR4 on circulating cells were blockaded [53,56] . In the bone marrow, discrete regions of the anoxic chamber are of increased SDF-1 expression and progenitor cell tropism [57] . Over the last ten years, the hypothesis that SDF-1/CXCR4 has a pivotal role in the biologic and physiologic functions of MSC received extensive support [58] .…”
Section: Discussionmentioning
confidence: 99%